2010
DOI: 10.1089/jpm.2009.0281
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Stages of Change Transtheoretical Model in End-of-Life Planning Conversations

Abstract: Reports in the end-of-life literature reveal that patients and health care professionals, including social workers, nurses, and physicians, avoid discussions about preparation for such care. End-of-life care discussion barriers include, but are not limited to, professionals feeling unprepared to have the discussions and patients' lack of readiness to discuss planning for this care. Another barrier is the lack of a structured framework to initiate these discussions, especially with clients with advanced illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 19 publications
1
21
0
Order By: Relevance
“…Previous studies have illustrated the applicability of the TTM to ACP, demonstrating the variability in individuals’ readiness to engage in different aspects of ACP, the process by which individuals move through stages of change, and the expected relationships between the TTM constructs, such as a decrease in the cons and an increase in the pros as individuals progress to later stages of readiness . The TTM has also been proposed as a useful framework for clinicians to use for ACP discussions . The materials developed in the current study were designed to reach beyond people who are ready and willing to engage in structured ACP discussions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have illustrated the applicability of the TTM to ACP, demonstrating the variability in individuals’ readiness to engage in different aspects of ACP, the process by which individuals move through stages of change, and the expected relationships between the TTM constructs, such as a decrease in the cons and an increase in the pros as individuals progress to later stages of readiness . The TTM has also been proposed as a useful framework for clinicians to use for ACP discussions . The materials developed in the current study were designed to reach beyond people who are ready and willing to engage in structured ACP discussions.…”
Section: Discussionmentioning
confidence: 99%
“…10 To date there has been little scrutiny of the effectiveness of ACP for children with life-threatening illnesses. Most of the existingliteratureisfromadultstudies, [11][12][13] with relatively few evaluating the quality of such communication for children. [14][15][16][17] We sought to understand barriers to ACD for children from the perspective of clinicians who work in settings where these discussions typically take place.…”
mentioning
confidence: 99%
“…This is particularly important when patients have repeat admissions to the hospital due to exacerbations, as their experiences may change their needs or preferences. Rizzo and colleagues 45 have recently found that the Stages of Change Transtheoretical Model is useful as a flexible way to handle end-of-life conversations, facilitating more meaningful communication. The review findings are congruent with Momen and colleagues' findings that patient preferences for end-of-life communication are highly individual, and health professionals need to facilitate such discussions based on patient wishes in COPD.…”
Section: Discussionmentioning
confidence: 99%